Diversificación de la oferta ecoturística y su influencia en la participación de la población local en la zona de Huayrapurina distrito de la Banda de Shilcayo - Coral Flores, Angely (2010)
Ecotourism diversification of ecological tourist Zone Huayrapurina reforestation as a social alternative, economic and ecological is a great opportunity for the involved association and tourist managers looking for innovation and diversification of the range of bids. The propose the develop of investigations for develop the ecotourism, through design of propose to ecotourism circuits that are pose like an alternative of diversification of the offert for companies that offert and a the sometime for the benefit of the responsible association of the Area Huayrapurina, generating income through Employment. The natural heritage conservation provides facilities to develop the practice of ecotourism, the region is not stranger to this reality as it has ecological zones such as the regional conservation mountain range. Escalera inside it is the Zone Huayrapurina that houses various natural and tourist. however they are not being property utilized, hinderíng the promotional of new tourist circuits so maintaining a rigid supply and preventy the local participation. Based on information compilation from direct sources. through surveys of domestic and foreing tourist, members of association of the study area, and interviews aimed a tourist managers and authorities tourist sector, the resutt was as a that diversification of the ecotourism bid influence positively participation of local people, achieving the awakeníng interest in the tourist sector, carries out ecotourist the opinion represents the acceptance of proposal for ecotourism circuits generating greater influx of tourists to the area of study and therefore work directly and indirectly for all involved. We obtained information from indirect Sources, such as websites and references that mention issves related to research work. This investigation aims to give an optimal alternative use of natural in this area, through ecotourism as a way to improve the quality life of the community it would give sustainable income for the association of Huayrapurina, for as many involved people as possible including private tour operators.